2012
DOI: 10.1159/000339637
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Transversal Two-Phase Study to Determine a National Prevalence of Epilepsy in Algeria

Abstract: Background/Aims: The prevalence of epilepsy in Algeria is unknown. The aims of this multicenter transversal study were to determine the national prevalence and clinical characteristics of epilepsy in the Algerian population. Methods: This two-phase study was conducted in 5 circumscriptions and included 8,046 subjects aged over 2 months who attended the randomly selected public and private primary care clinics. In the phase 1 study, a questionnaire was submitted to the sample of patients. In the phase 2 study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In Algeria, where the prevalence of epilepsy is estimated at 8.32/1000 (Moualek et al, 2012) and the rate of inbreeding at 38% (18% in Oran) (Fondation, 2007), very few epidemiological studies on epilepsy have been published and none has evaluated the association with risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In Algeria, where the prevalence of epilepsy is estimated at 8.32/1000 (Moualek et al, 2012) and the rate of inbreeding at 38% (18% in Oran) (Fondation, 2007), very few epidemiological studies on epilepsy have been published and none has evaluated the association with risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…15 In one study from Algeria, the prevalence rate was reported to be 8.32 per 1000. 21 In one study from Turkey, 22 the prevalence of active epilepsy was 5 per 1000 inhabitants. In a comparative epidemiology of epilepsy in Pakistan and Turkey, 23 the prevalence rate of epilepsy was 9.98 in 1000 people in Pakistan and 7.0 in 1000 persons in Turkey.…”
Section: Prevalence Of Tle In Qatarmentioning
confidence: 99%